Transformative Pathways of Agrarian Reform: Comparative Bibliometric Insights of Southeast Asia and Indonesia Cases - Dewi Gafuraningtyas; Raldi Hendro Koestoer; Hafid Setiadi; Mohammad Ridwan Lessy (The Journal of Indonesia Sustainable Development Planning, 2024)
Agrarian reform is recognized globally as a solution for reducing land ownership inequality. Many countries, including Indonesia, are still working to enhance its implementation. This study examines global agrarian reform research trends over the past decade, focusing on Southeast Asian (SEA) nations, particularly Indonesia. The methodology involved conducting a bibliometric analysis using RStudio and adhering to the PRISMA framework. The result of our analysis, which included 248 articles, reveals a trend of increasing interest in agrarian reform. Among the 20 selected articles, we observe that agrarian reform success in Europe, especially in Scandinavia, correlates with democratization. Conversely, Latin America contends with personal agenda challenges, while Africa faces issues of inclusivity and gender. SEA nations employ diverse approaches: Vietnam boosts productivity with private farming, Thailand enhances revenue through agrotourism, but Timor-Leste and the Philippines face managerial and credit access hurdles. Indonesia integrates asset and access management, yet access issues persist.